Statins and cognition: Modifying factors and possible underlying mechanisms - Jamshidnejad-Tosaramandani, Tahereh; Kashanian, Soheila; Al-Sabri, Mohamed H.; Kročianová, Daniela; Clemensson, Laura E.; Gentreau, Mélissa; Schiöth, Helgi B. (Frontiers in Aging Neuroscience, 2022)
Statins are a class of widely prescribed drugs used to reduce low-density lipoprotein cholesterol (LDL-C) and important to prevent cardiovascular diseases (CVD). Most statin users are older adults with CVD, who are also at high risk of cognitive decline. It has been suggested that statins can alter cognitive performance, although their positive or negative effects are still debated. With more than 200 million people on statin therapy, it is crucial to understand the reasons behind discrepancies in the results of these studies. Here, we review the effects of statins on cognitive function and their association with Alzheimer's Disease (AD). First, we summarized the main individual and statin-related factors that could modify the cognitive effects of statins. Second, we proposed the underlying mechanisms for the protective and adverse effects of statins on cognitive performance and AD. Finally, we discussed potential causes of discrepancies between studies and suggested approaches to improve future studies assessing the impact of statins on AD risk and cognitive function.